Tính:
\(\sqrt{105}.\left(\sqrt{\frac{15}{7}}-\sqrt{\frac{35}{3}}+\sqrt{\frac{21}{5}}\right)\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{\left(\frac{1}{14}-\frac{\sqrt{2}}{7}+\frac{3\sqrt{2}}{35}\right).\frac{-4}{15}}{\left(\frac{1}{10}+\frac{3\sqrt{2}}{25}-\frac{\sqrt{2}}{5}\right).\frac{5}{7}}\)
\(=\frac{\frac{1}{7}\left(\frac{1}{2}-\sqrt{2}+\frac{3\sqrt{2}}{5}\right).\frac{-4}{15}}{\frac{1}{5}\left(\frac{1}{2}+\frac{3\sqrt{2}}{5}-\sqrt{2}\right).\frac{5}{7}}\)
\(=\frac{\frac{1}{7}.\frac{-4}{15}}{\frac{1}{5}.\frac{5}{7}}=\frac{\frac{-4}{105}}{\frac{1}{7}}=\frac{-4}{15}\)
\(\frac{\left(\frac{1}{14}-\frac{\sqrt{2}}{7}+\frac{3.\sqrt{2}}{35}\right).\frac{-4}{15}}{\left(\frac{1}{10}+\frac{3.\sqrt{2}}{25}-\frac{\sqrt{2}}{5}\right).\frac{5}{7}}\)
\(=\frac{\left(\frac{1}{14}-\frac{\sqrt{2}}{7}+\frac{3.\sqrt{2}}{35}\right).\frac{-4}{15}}{\frac{1}{10}.\frac{5}{7}+\frac{3.\sqrt{2}}{25}.\frac{5}{7}-\frac{\sqrt{2}}{5}.\frac{5}{7}}\)
\(=\frac{\left(\frac{1}{14}-\frac{\sqrt{2}}{7}+\frac{3.\sqrt{2}}{35}\right).\frac{-4}{15}}{\frac{1}{14}+\frac{3.\sqrt{2}}{35}-\frac{\sqrt{2}}{7}}\)
\(=\frac{-4}{15}\)
Học tốt
a) Ta có: \(A=\sqrt{8-2\sqrt{15}}\cdot\left(\sqrt{3}+\sqrt{5}\right)-\left(\sqrt{45}-\sqrt{20}\right)\)
\(=\sqrt{5-2\cdot\sqrt{5}\cdot\sqrt{3}+3}\cdot\left(\sqrt{5}+\sqrt{3}\right)-\sqrt{5}\left(\sqrt{9}-\sqrt{4}\right)\)
\(=\sqrt{\left(\sqrt{5}-\sqrt{3}\right)^2}\cdot\left(\sqrt{5}+\sqrt{3}\right)-\sqrt{5}\)
\(=\left|\sqrt{5}-\sqrt{3}\right|\cdot\left(\sqrt{5}+\sqrt{3}\right)-\sqrt{5}\)
\(=\left(\sqrt{5}-\sqrt{3}\right)\cdot\left(\sqrt{5}+\sqrt{3}\right)-\sqrt{5}\)(Vì \(\sqrt{5}>\sqrt{3}\))
\(=5-3-\sqrt{5}\)
\(=2-\sqrt{5}\)
b) Ta có: \(B=\left(\frac{\sqrt{21}-\sqrt{3}}{\sqrt{7}-1}-\frac{\sqrt{15}-\sqrt{3}}{1-\sqrt{5}}\right)\left(\frac{1}{2}\sqrt{6}-\sqrt{\frac{3}{2}}+3\sqrt{\frac{2}{3}}\right)\)
\(=\left(\frac{\sqrt{3}\left(\sqrt{7}-1\right)}{\sqrt{7}-1}+\frac{\sqrt{3}\left(\sqrt{5}-1\right)}{\sqrt{5}-1}\right)\left(\sqrt{\frac{3}{2}}-\sqrt{\frac{3}{2}}+\sqrt{6}\right)\)
\(=\sqrt{3}+\sqrt{3}+\sqrt{6}\)
\(=2\sqrt{3}+\sqrt{6}\)
c) Ta có: \(C=2\sqrt{3}+\sqrt{7-4\sqrt{3}}+\left(\sqrt{\frac{1}{3}}-\sqrt{\frac{4}{3}}+\sqrt{3}\right):\sqrt{3}\)
\(=2\sqrt{3}+\sqrt{4-2\cdot2\cdot\sqrt{3}+3}+\sqrt{\frac{1}{3}:3}-\sqrt{\frac{4}{3}:3}+\sqrt{3:3}\)
\(=2\sqrt{3}+\sqrt{\left(2-\sqrt{3}\right)^2}+\sqrt{\frac{1}{9}}-\sqrt{\frac{4}{9}}+\sqrt{1}\)
\(=2\sqrt{3}+\left|2-\sqrt{3}\right|+\frac{1}{3}-\frac{2}{3}+1\)
\(=2\sqrt{3}+2-\sqrt{3}+\frac{2}{3}\)(Vì \(2>\sqrt{3}\))
\(=\sqrt{3}+\frac{8}{3}\)
d) Ta có: \(D=\left(\frac{5+\sqrt{5}}{5-\sqrt{5}}+\frac{5-\sqrt{5}}{5+\sqrt{5}}\right):\frac{1}{\sqrt{7-4\sqrt{3}}}\)
\(=\left(\frac{\left(5+\sqrt{5}\right)^2+\left(5-\sqrt{5}\right)^2}{\left(5-\sqrt{5}\right)\left(5+\sqrt{5}\right)}\right)\cdot\sqrt{4-2\cdot2\cdot\sqrt{3}+3}\)
\(=\frac{25+10\sqrt{5}+5+25-10\sqrt{5}+5}{25-5}\cdot\sqrt{\left(2-\sqrt{3}\right)^2}\)
\(=\frac{60}{20}\cdot\left|2-\sqrt{3}\right|\)
\(=3\cdot\left(2-\sqrt{3}\right)\)(Vì \(2>\sqrt{3}\))
\(=6-3\sqrt{3}\)
Lời giải:
\(\sqrt{105}(\sqrt{\frac{15}{7}}-\sqrt{\frac{35}{3}}+\sqrt{\frac{21}{5}})=\sqrt{3.5.7}(\sqrt{\frac{3.5}{7}}-\sqrt{\frac{5.7}{3}}+\sqrt{\frac{3.7}{5}})\)
\(=\sqrt{(3.5)^2}-\sqrt{(5.7)^2}+\sqrt{(3.7)^2}=3.5-5.7+3.7=1\)